'I don't think anybody explained to me how it works': qualitative study exploring vaccination and primary health service access and uptake amongst Polish and Romanian communities in England. Issue 7 (9th July 2019) - Bell, Sadie; Edelstein, Michael; Zatoński, Mateusz; Ramsay, Mary; Mounier-Jack, Sandra
Abstract : Objectives: This study explored vaccination attitudes and behaviours among Polish and Romanian communities, and related access to primary healthcare services. Design: A qualitative study using in-depth semistructured interviews with Polish and Romanian community members (CMs) and healthcare workers (HCWs) involved in vaccination in areas with large Polish and Romanian communities. CMs discussed their vaccination attitudes and their experiences of accessing vaccinations in England. HCWs shared their experiences in vaccinating Polish and Romanian communities. Setting: Recruitment focused on three geographical areas in England with large Polish and Romanian populations (in London, Lincolnshire and Berkshire). Participants: 20 Polish and 10 Romanian CMs, and 20 HCWs. Most CMs were mothers or pregnant women and were recruited from London or Lincolnshire. HCWs included practice nurses, health visitors and school nurses recruited from the targeted geographical areas. Results: Although most CMs reported vaccinating according to the UK schedule, obstacles to vaccination were highlighted. CMs experienced difficulties navigating and trusting the English primary healthcare system, and challenges in accessing credible vaccination information in Polish and Romanian. CM vaccination expectations, largely built on knowledge and experiences from Poland and Romania, were often unmet. This was driven by differences in vaccination scheduling and service provision in England, such as nurses delivering vaccines instead of doctors. CMs reported lower acceptance of the influenza vaccine, largely due to perceptions around the importance and efficacy of this vaccine. HCWs reported challenges translating and understanding vaccination histories, overcoming verbal communication barriers and ensuring vaccination schedule completeness among families travelling between England and Poland or Romania. Conclusions: This study identified vaccination uptake and delivery issues and recommendations for improvement. HCWs should discuss health service expectations, highlight differences in vaccination scheduling and delivery between countries, and promote greater understanding of the English primary healthcare system in order to encourage vaccination in these communities.